KAJIAN PENGELOLAAN MODAL KERJA PERUSAHAAN - Sophan Syaiful (Business Perspective Journal, 2021)
Working Capital has an important benefit for a company because it has a close relationship with the daily activities of a company. This working capital must be maintained so as not to overdo it and not lack, it will affect tehadap companies concerned. , in addition to maintaining the company's survival. The purpose of this study is to analyze the effectiveness of working capital management at CV. Mosal Graphic. The problem studied is the effective or ineffective working capital management and the hypothesis proposed is that CV. Mosal Grafika has not conducted effective working capital management in its operations. To know the effective and effective working capital management is used by using the analysis of financial ratios. The calculation results obtained based on the analysis of working capital requirements CV. The conclusion that can be taken is that CV. Mosal Grafika has not conducted effective working capital management in its business operation or it can be concluded that the researcher's hypothesis is accepted. Keywords: Working capital